Diagnóstico del deterioro de puentes en la Zona 6-1, San Carlos Este - Zamora-Chaves, Steffany (Instituto Tecnológico de Costa Rica, 2010)
This project basically consists of the diagnosis of the deterioration of bridges located to the east of San Carlos, zone 6-1. The objective of this project focused mainly in the realization of an analysis to look for the establishment of the deterioration causes, the degree of damage so far, and the way to reinforce or partially rebuilt some of the most affected bridges in the zone 6-1. Talking about the methodology used to complete this study over the bridges in San Carlos, consultation to the Manual of Inspection of Bridges used in Peru were done, which allow us to compare it against the one used in Costa Rica by the Direction of Bridges of the MOPT. In this way similarities and differences were found which came to enrich the methods used to evaluate and identify damages to the bridges during this work. On the other hand, field visits were carried on with the intention of integrate ourselves into the evaluation process and to have a real notion of the damages and causes of these in the bridges of the national road network, as well as to generate a database, classifying the structures, taking into account the type of material, length and nature of the damage. To the date of September 2009, thirty-three (33) bridges have been documented with their respective deficiencies, and to those bridges that were possible, technical proposals have been given to obtain optimal operation again. The deterioration of the bridge structures in this zone are due mainly to the lack of maintenance, which is related unquestionable to the limited resources destined to this area in San Carlos. The main identified damages are problems of undermining in bastions, corrosion, oxidation and deterioration of the beams of concrete.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2010.
Keywords: Puente; Superestructura; Socavación; Filtración; Subestructura